Hypertensive disease of pregnancy. I. Maternal Risk - Ruiz I., Julián (2015)
A cohort study of 418 patients with EHE (hypertensive disease of pregnancy) treated at the General Hospital Base Cayetano Heredia between January 1980 to June 1982. Applying the diagnostic parameters of EHE is presented. 191 (45.7%) had a confirmed diagnosis and 227 (54 .3%) or clinical diagnosis of disease prevention. The highest incidence of the disease in pregnant women under 25 years is borne predominantly primigravid, highlighting the importance of prenatal care to reduce maternal morbidity and mortality. EHE is associated with high rates of cesarean section (28.7%) and is an important cause of puerperal morbidity (anemia and infections) with a high rate of maternal mortality (0/000 237).